2014
DOI: 10.1038/nn.3822
|View full text |Cite
|
Sign up to set email alerts
|

Social learning and amygdala disruptions in Nf1 mice are rescued by blocking p21-activated kinase

Abstract: Children with Neurofibromatosis type 1 (NF1) are increasingly recognized to have high prevalence of social difficulties and autism spectrum disorders (ASD). We demonstrated selective social learning deficit in mice with deletion of a single Nf1 gene (Nf1+/−), along with greater activation of mitogen activated protein kinase pathway in neurons from amygdala and frontal cortex, structures relevant to social behaviors. The Nf1+/− mice showed aberrant amygdala glutamate/GABA neurotransmission; deficits in long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
107
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 43 publications
9
107
3
Order By: Relevance
“…However, in contrast to the previous findings (Cui et al, 2008;Shilyansky et al, 2010a), Molosh and colleagues reported that glutamatergic transmission is also altered in the amygdala of Nf1 +/-mice (Molosh et al, 2014). This discrepancy might be due to the differences in genetic backgrounds of the mutants: an F1 hybrid (C57Bl/6 x 129S6) was used in the previous studies (Cui et al, 2008;Shilyansky et al, 2010a) whereas a C57Bl/6 background was used by Molosh et al (2014). Nevertheless, these results clearly show that NF1 regulates neurotransmitter release from GABAergic inhibitory neurons (Fig.…”
Section: Rui Costa Found That Inhibitory Synaptic Transmission Is Enhcontrasting
confidence: 62%
See 2 more Smart Citations
“…However, in contrast to the previous findings (Cui et al, 2008;Shilyansky et al, 2010a), Molosh and colleagues reported that glutamatergic transmission is also altered in the amygdala of Nf1 +/-mice (Molosh et al, 2014). This discrepancy might be due to the differences in genetic backgrounds of the mutants: an F1 hybrid (C57Bl/6 x 129S6) was used in the previous studies (Cui et al, 2008;Shilyansky et al, 2010a) whereas a C57Bl/6 background was used by Molosh et al (2014). Nevertheless, these results clearly show that NF1 regulates neurotransmitter release from GABAergic inhibitory neurons (Fig.…”
Section: Rui Costa Found That Inhibitory Synaptic Transmission Is Enhcontrasting
confidence: 62%
“…A recent study also reported deficits in social behavior, increased GABAergic synaptic transmission, and impaired amygdala LTP in the Nf1 +/-mice (Molosh, Johnson, Spence, Arendt, Federici, Bernabe et al, 2014). However, in contrast to the previous findings (Cui et al, 2008;Shilyansky et al, 2010a), Molosh and colleagues reported that glutamatergic transmission is also altered in the amygdala of Nf1 +/-mice (Molosh et al, 2014). This discrepancy might be due to the differences in genetic backgrounds of the mutants: an F1 hybrid (C57Bl/6 x 129S6) was used in the previous studies (Cui et al, 2008;Shilyansky et al, 2010a) whereas a C57Bl/6 background was used by Molosh et al (2014).…”
Section: Rui Costa Found That Inhibitory Synaptic Transmission Is Enhmentioning
confidence: 84%
See 1 more Smart Citation
“…Decrease of Nf1 induces deficits in hippocampal-dependent spatial learning, amygdala dependent-social learning and prefrontal cortex-dependent working memory by increasing GABA release in these different areas of the brain through the activation of the Ras–ERK pathway61626364. The increase of Ras thus appears to produce opposite effects on GABA neurotransmission depending upon whether it is associated with Syngap1 or Nf1 haploinsufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Molosh et al 16 identified the amygdala as a key structure involved in social learning deficits in NF1+/ − mice. They found aberrant glutamate and GABA neurotransmission in BLA (basolateral amygdala nuclei) neurons in NF1+/ − mice resulting in functional changes in amygdala networks.…”
Section: Discussionmentioning
confidence: 99%